Microstructural and Mechanical Properties of Ti3SiC2-CNF Composite Materials by PM - GARİBA, Abdualkarim Musbah M.; OKAY, Faik; SAİD, Ibtesam Said Shneeb; ISLAK, Serkan (Politeknik Dergisi, 2021)
This study aims to investigate the microstructure and mechanical properties of Ti3SiC2-carbon nanofiber (CNF) composite materials by powder metallurgy (PM). Ti, SiC, graphite and CNF powders were used to produce Ti3SiC2-CNF composite materials. After formulated powders were ground in a ball mill, the milled powders were pressed at 500 MPa pressure and then sintered at 1150 °C, 1300 °C and 1450 °C. SEM-EDS and XRD analysis were used to examine the microstructure and phase formation. Hardness test was carried out with the help of Vickers hardness test apparatus. The densities were measured by Archimedes’ principle. Three-point bending test was performed to determine the transverse rupture strength (TRS) of the samples. SEM images showed that the samples have kink band and nanolaminar structures typical of MAX phase materials. The presence of Ti3SiC2 phase detected by XRD analysis also supports this situation. Depending on the sintering temperature, there were changes in the microstructure, density and mechanical properties of the samples.
Keywords: Engineering; Ti3SiC2; CNF; MAX phase; microstructure; hardness; TRS; Mühendislik